Formation of Gas Hydrates in the Field of Crude Oil Refining: Najaf Refinery (Unit 2) / Case Study - Shattab, Samer N.; Hussain, Mohammad N.; Gabbar, Ghalib S.; Raheem, Hayder S. (Journal of Petroleum Research and Studies, 2024)
Gaseous hydrates are defined as (clathrates) consisting of three basic components (crude liquid, gas, and water). When the gas (guest) is liberated from the raw liquid by the concepts of dynamic and thermal movement of gas and liquid, the (gas) is confined inside the cage of the evaporating water bubble (the host) to form gaseous hyder due to the conditions of heat and pressure in the form of a spherical crystalline structure linked by hydrogen bonds under the van der Waals force effect. Hydrates, when they occur, cause total or partial blockage and obstruction of the flow of crude oil and loss of operational capacity. It depends on the type of gaseous hydrate formed and the nature of the local conditions. Therefore, gaseous hydrates are considered one of the most important local scientific problems that crude oil refineries suffer from, especially in the two locations, starting from the primary heating area - heat exchangers package (EX-211ABC) all the way to the heating area Secondary - (the unit's furnace). The present study discusses in detail the. most important scientific and practical solutions, and through the results it was found that the technical practical steps adopted by the operators of the refining units cause future damage and reduce the design life of the unit, in contrast to the scientific solutions. The paper discusses the most important issues and related analyzes that predict the occurrence of hydrates to reduce or limit the impact of the occurrence of gaseous hydrates by relying on the following checks (Rvp, salt content, sediment and water). In short, the aim of this paper is to identify behaviors and discuss problems and solutions gas hydrates in crude oil refineries (Najaf Refinery - unit 2) specifically in the second heating area (Branch-B 105 thermal unit furnace), the paper shows complete information in a concise form for operators and engineers of the crude oil refining sector.